Deposition of Au nanoparticles inside porous CeO2 nanocubes using Langmuir-Blodgett technique - Das, Subhasis; Bhattacharjee, Gourab; Satpati, Biswarup; Kumar, Mukesh; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal of Chemistry, 2018)
Porous 3D CeO2 nanocubes were synthesized using hot injection technique. These nanocubes were able to form a stable monolayer over water and HAuCl4 subphase in Langmuir-Blodgett (LB) trough due to the presence of surface capped oleic acid and oleylamine. CeO2-Au nanocomposites were synthesized exploiting the ability of oleylamine to reduce AuCl4 ions to Au-0, via LB method. CeO2 nanocubes gave rise to excellent long-range assembly at air/water interface and gold nanoparticles were formed inside these porous nanocubes without disturbing this arrangement. The formation of a stable monolayer was evidenced from the surface pressure-area (P-A) isotherm. The development of Au nanoparticles was confirmed with great effort from a comprehensive study using UV-Vis spectroscopy, XRD, XPS, FTIR, TEM, STEM, EDX, tomography and chemical mapping.

Dexterous route for synthesis of hollow spherical ZnO and ZnO-Ag nanocomposite with superior photocatalytic ability - Maity, Jayeta; Bhattacharjee, Gourab; Satpati, Biswarup; Sardar, Debasmita; Ghosalya, Manoj Kumar; Bala, Tanushree (ChemistrySelect, 2019)
Hollow spherical ZnO and hollow ZnO-Ag nanocomposites with variable percentage of loading of Ag content were successfully fabricated through a novel, template free and easily reproducible route. Extensive characterizations were carried out using FTIR, XRD, XPS, BET, TEM and SEM. The hollow morphology of the particle and the composite encouraged a detailed photocatalysis study in comparison to solid commercial ZnO and the corresponding ZnO-Ag composite. The photocatalytic activity of the hollow particle and the composite was assessed monitoring the decolouration of methylene blue dye using UV-Vis absorption spectroscopic technique. An increased surface area for hollow morphology as compared to solid particles established a conspicuous boost in photocatalytic activity.
Keywords: excellent photocatalysis; synthesis; template free; ZnO hollow nanoparticles; ZnO-Ag nanocomposite